The replication crisis as mere indicator of two fundamental misalignments: methodological confirmation bias in hypothesis testing and anthropological oversimplification in theory-building - Schnepf, Julia; Groeben, Norbert (New ideas in psychology, 2024)
Psychological research is currently in a phase of transition. The replication crisis has led to the introduction of a number of corrective measures such as preregistration, registered reports, open data and methods in order to make scientific knowledge in psychological science more reliable. In this article, we discuss why these tools remain superficial and provide rather a symptom treatment than a deeper treatment of the causes of the replication crisis. To this end, we address two central misalignments of current psychological research: Confirmation bias, in the sense of overweighting significant, hypothesis-confirming findings over negative ones, and the anthropological oversimplification of the human research subject. We conclude by providing indications of how a paradigm shift in psychological science research and publication practices can help to combat the causes of the replication crisis and poor scientific research practices.
Online verfügbar: 1. August 2024, Artikelversion: 1. August 2024
Gesehen am 07.04.2025